2017
DOI: 10.1111/apa.13832
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of maternal voice interventions demonstrates increased stability in preterm infants

Abstract: We systematically reviewed how effectively maternal voice interventions supported the clinical outcomes and development of preterm infants. A total of 512 preterm infants were included in 15 studies with different designs, from January 2000 to July 2015. Live and recorded maternal voice interventions were associated with the physiologic and behavioural stabilisation of preterm infants, with fewer cardiorespiratory events, but the evidence was insufficient to evaluate the long-term effects. Well-defined determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 55 publications
(153 reference statements)
3
69
0
5
Order By: Relevance
“…While the benefit of having the mother physically present is unquestionable, it may not be feasible for mothers to remain at their infant's bedside all day, in which case the use of recorded maternal voices may provide a valuable supplement (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…While the benefit of having the mother physically present is unquestionable, it may not be feasible for mothers to remain at their infant's bedside all day, in which case the use of recorded maternal voices may provide a valuable supplement (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there has been an increased interest in introducing music interventions in neonatal intensive care units (NICU). A number of authors have considered the effects of music listening in preterm infants and many have shown stabilizing effects on heart and respiratory rates, reduction of apnea or bradycardia, improved resting energy expenditure, improved feeding, better weight gain and more mature sleep patterns; and most of them report a beneficial effect on at least one of these outcomes (Haslbeck, 2012;Filippa et al, 2017;Pineda et al, 2016;Anderson and Patel, 2018). Nevertheless, these music interventions have been proposed for enhancing neonatal intensive care environments without knowing the preterm brains ability to process music.…”
Section: Introductionmentioning
confidence: 99%
“…Much research is needed in this area due to the heterogeneous nature of the studies. (17,18). Most studies on the effects of maternal voices used recorded stimuli and showed, for example, that preterm infants experienced fewer episodes of feeding intolerance and achieved full enteral feeds in fewer days when exposed to recordings of their mother's voice (19).…”
Section: Key Notesmentioning
confidence: 99%
“…So far, two reviews on the effects of maternal voice in the NICU have been carried out. Maternal voice has been shown to have short‐term clinical benefits, such as physiological and behavioural stabilisation of preterm infants . Most studies on the effects of maternal voices used recorded stimuli and showed, for example, that preterm infants experienced fewer episodes of feeding intolerance and achieved full enteral feeds in fewer days when exposed to recordings of their mother's voice .…”
Section: Introductionmentioning
confidence: 99%